Identitas nasional dalam dinamika globalisasi dan tantangan integrasi nasional di indonesia - Anjani, Erida (Maliki Interdisciplinary Journal, 2025)
National identity is the character of a nation that reflects its values, culture, and history. In the era of globalization, Indonesia's national identity faces challenges that threaten the unity and sovereignty of the nation. This article examines the functions of national identity, influencing factors, and the strategic role of Pancasila in strengthening national integration. Using literature review and qualitative approach, this study aims to enhance public understanding of the importance of preserving national identity as a foundation for national unity. The findings highlight that strengthening Pancasila values, civic education, and cultural preservation are key strategies to face globalization dynamics. These strategies are expected to sustain national integration and reinforce Indonesia's position as an independent and dignified country.